Application of the Balanced Scorecard for strategy reformulation: Perspectives from a Canadian municipality. (26th August 2021) - Sayed, Naqi; Lento, Camillo; Henderson, Michelle
Abstract: This study explores the application of the Balanced Scorecard (BSC) for strategy reformulation and performance measurement of a Canadian municipality. This study is motivated by the trend of performance management tools becoming more commonplace in the municipal sector, due to the New Public Management paradigm. Interviews with key stakeholders were conducted to determine Key Success Factors (KSFs). A survey of broad stakeholders was used to determine the importance of the KSFs and their multidimensional causal relationships, using a multiple‐criteria, decision‐making method. We find that economic growth plays a central role in the municipality's strategy, and it is perceived to be primarily driven by management leadership, in addition to economic diversity, Indigenous relationships, and increasing the tax base. Résumé: Les auteures de cette étude se penchent sur l'application du tableau de bord prospectif (TBP) à la reformulation de la stratégie et à la mesure du rendement d'une municipalité canadienne. L'étude est motivée par le fait que les outils de gestion de la performance deviennent de plus en plus courants dans le secteur municipal, notamment en raison du paradigme de la Nouvelle gestion publique. Les auteures de l'étude cherchent à établir les facteurs clés de succès (FCS) grâce à des entretiens auprès des principales parties prenantes. Cette enquête a permis d'établir l'importance des facteurs clés de succès et de leurs relations causales multidimensionnelles, grâce à une méthode de prise de décision à critères multiples. Il ressort des résultats que la croissance économique joue un rôle central dans la stratégie de la municipalité et qu'elle est perçue comme étant principalement déterminée par le leadership de la direction, la diversité économique, les relations avec les autochtones et l'augmentation de l'assiette fiscale.